Bring it on : the complete story of the cheerleading movie that changed, like, everything (no, seriously) - Wickman, Kase (Chicago Review Press, 2023)
Opening at the number one spot in North American theaters in August 2000, Bring It On, the little cheerleading movie that could, went on to earn a worldwide gross of approximately $90 million, cementing the careers of Gabrielle Union, Kirsten Dunst, and Eliza Dushku--not to mention establishing a toothbrush as the sexiest household object, introducing instantly iconic quotes and cheers, and achieving "Oh, I love that movie!" status. The first-time director who helmed the movie, Peyton Reed, now has multiple smash-hit Marvel films under his belt. Bring It On spawned a half-dozen sequels, a Tony nominated musical, and a whole new genre of female-led films. Not bad for a movie that almost didn't get greenlit in the first place. With the support of the Bring It On filmmakers, author and pop culture expert Kase Wickman accessed Universal Studios' archives and conducted new interviews with cast, crew, and more for a full reveal of all the stories fans will love in this complete examination of the greatest cheerleading movie almost never made, and why it still matters today.